Price and Quality Analysis of Purchasing Decision Making at Rocket Chicken Mojokrapak Jombang - Ino Angga Putra; Abdulloh Chumaidi; Khotim Fadhli (INCOME: Innovation of Economics and Management, 2022)
The purpose of the study was to determine the effect of price and product quality on purchasing decisions at Rocket Chicken Jombang. This study uses quantitative research methods, using the type of multiple linear regression. This research uses survey research method. the population in this study are consumers at Rocket Chicken Tembelang Jombang. The sampling method used was accidental sampling. The samples taken in this study were 50 respondents, namely consumers of Rocket Chicken Tembelang Jombang. The data used are primary and secondary data. Collecting data through activities, namely a) distributing questionnaires, b) interviews with interviewees with interview instruments, c) documentation in the form of writing or pictures, and d) literature review for the purposes of preparing reports. The data processing of the results of this study uses the type of multiple linear regression. The results obtained indicate that the price has a significant effect on purchasing decisions at rocket chicken tembelang jombang, this is evidenced by the t-count value of 5.029 with a significance level of 0.000 < from 0.005. Food quality has no significant effect on purchasing decisions at rocket chicken tembelang jombang, this is evidenced by the t-count value of 2,343 with a significance level of 0.023 > from 0.005.